Low Toe-Brachial Indices are Associated with Saccular Intracranial Aneurysms - Kangas, Essi; Rantasalo, Ville; Korpisalo, Petra; Kuusela, Aino M.; Hakovirta, Eelis; Korhonen, Paivi Elina; Rahi, Melissa; Kivelev, Juri; Rinne, Jaakko; Venermo, Maarit; Hirvonen, Jussi; Hakovirta, Harri; et al. (Informa UK Limited, 2026)
Purpose: Peripheral artery disease (PAD) is a manifestation of systemic atherosclerosis. Non-invasive lower-limb pressure indices, such as the ankle-brachial index (ABI) and toe-brachial index (TBI), are widely used in the diagnostic evaluation of PAD and are strongly associated with atherosclerotic cardiovascular diseases. Intracranial aneurysms (IAs) share common risk factors with atherosclerotic cardiovascular diseases, particularly smoking and hypertension. In previous research, we found that a low ABI is associated with a higher prevalence of unruptured IAs. The objective of the present study is to examine whether low TBI is similarly associated with a prevalence if IAs.
Patients and Methods: This retrospective cohort study included patients (n=2751) who underwent a TBI assessment at a tertiary hospital between January 2011 and December 2013. The patients with available cerebrovascular imaging or a confirmed diagnosis of ruptured saccular IA (n = 776) were included into the study. The potential association between TBI and the prevalence of saccular IAs was the main outcome of interest.
Results: Patients were stratified according to their TBI values as follows: low TBI (< 0.5; n=473), borderline TBI (0.50- 0.69; n=180), and normal TBI (>= 0.7; n=123).The prevalence of unruptured IAs was 16.3% in the low TBI group, 8.3% in the borderline TBI group, and 4.1% in the normal TBI category (p< 0.001). Sex- and age-adjusted multinomial regression including clinically relevant variables revealed that low TBI (odds ratio [OR], 3.59; 95% confidence interval [CI], 1.39- 9.27), female sex (OR, 1.68; 95% CI, 1.06- 2.673), and smoking history (OR, 2.56; 95% CI, 1.393- 4.695) were associated with the prevalence of unruptured IAs.
Conclusion: Low TBI was associated with a fourfold higher prevalence of unruptured IAs compared with normal TBI. In this retrospective cohort, the strongest association remained between low TBI and unruptured IAs after adjustment for established IA risk factors. These finding support a potential role of atherosclerosis in IA formation. Prospective studies are warranted to clarify the temporal relationship and to evaluate whether TBI could contribute to risk stratification in patients at risk of intracranial aneurysms.